2003
DOI: 10.1007/bf02344881
|View full text |Cite
|
Sign up to set email alerts
|

Optimum electrode configuration for detection of arm movement using bio-impedance

Abstract: A four-channel impedance measurement system, including a two-channel goniometer, to analyse human arm movement, was constructed. Impedances and joint angles were simultaneously measured for wrist and elbow movements. As the impedance changes resulting from wrist and elbow movements depended heavily on electrode placement, the optimum electrode configurations for those movements were determined by searching for high correlation coefficients, large impedance changes and minimum interferences in ten subjects (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 4 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…It is possible that the appropriate position of BI electrodes should be considered for accurate estimation of BI change. Kim, et al (2003) measured BI during exercises with electrodes in various positions and reported the importance of selecting a derivation area where BI changes that arise as a result of movements can be accurately evaluated. The possibility exists that BI depends on the arrangements of such tissues as muscle, tendon and blood vessels where the BI electrodes are attached (Foster and Lukaski.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the appropriate position of BI electrodes should be considered for accurate estimation of BI change. Kim, et al (2003) measured BI during exercises with electrodes in various positions and reported the importance of selecting a derivation area where BI changes that arise as a result of movements can be accurately evaluated. The possibility exists that BI depends on the arrangements of such tissues as muscle, tendon and blood vessels where the BI electrodes are attached (Foster and Lukaski.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura, et al (1992) and Kim, et al (2003) demonstrated that joint angle and electromyography (EMG) are related to changes in BI. This indicates that changes in muscle length and the force exerted by muscle contraction relate to BI recordings.…”
Section: Introductionmentioning
confidence: 99%
“…The CFS was then attached to two positions denoted as 1 of 3 and 2 of 3 from the hip joint on the upper side and to three positions denoted as 1 of 4, 2 of 4, and 3 of 4 from the knee joint on the lower side in turns. These positions are based on optimum positions for measuring the bio-impedance of the lower limbs using the standard disposable electrodes [2] and [3]. …”
Section: Methodsmentioning
confidence: 99%
“…There have been many studies that utilize the bio-impedance measurement method to analyze the movements of the upper and lower limbs [2] and [3]. A fixed electrical current flows into the limbs through four standard disposable electrodes in this method.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal electrode pairs were determined by using the following criteria: (1) a high correlation coefficient between impedance and joint angle, (2) high SNR (signal to noise ratio) of impedance changes, where the signal is the magnitude of the impedance change and noise is the impedance change resulting from the interferences mentioned below [8]. Fig.…”
Section: Criteria For Selecting Optimal Electrode Configurationsmentioning
confidence: 99%